Collembola community structure under different land management in subtropical Brazil - de Oliveira Filho L.C.I.* (2020)
© 2020 Association of Applied BiologistsTillage systems in conservation agriculture such as no-tillage (NT) and crop-livestock integration (CLI) have been proposed to limit the negative impacts of intensive agriculture. Soil organisms such as Collembola are good indicators because they respond to a variety of environmental and ecological factors and their community structure indicates a change in land management. In this study, we propose to assess the relationships between springtail biodiversity in management systems with a history of NT and CLI. For both management systems, nine points were sampled, distributed in a 30 × 30 m sampling grid, in three municipalities on the Southern Santa Catarina Plateau, Brazil. Springtails were collected using a metal cylinder (5 cm diameter × 5 cm deep) and identified at the species level. At the same point, samples were collected to evaluate soil properties (chemical, physical and microbiological). In total, 538 individuals were collected, distributed in 24 species, 293 individuals (18 species) in NT and 245 individuals (17 species) in the CLI system. Soil management systems studied did not affect the total number of individuals and richness. The NT system had a greater association with epigeic species, while the CLI system was more associated with hemiedaphic and edaphic species, which is related to the site-specific differences in soil conditions. In both soil management systems, the species were influenced by a range of soil properties. The species Isotomurus sp. 1 and Lepidocyrtus sp. 1 were more influenced by soil properties in the NT system, while the species Proisotoma sp. 1, Sminthurinus sp. 1 and Tullbergia antarctica were more influenced by soil properties in the CLI system, compared to the others. Collembola community structure and species diversity were modified by the soil management systems. Our results suggest that the Collembola community may indicate changes across land management systems in conservation agriculture.